Kimbanguism: Prophetic Christianity in Congo - Fehderau, Harold W. (Practical Anthropology, 1962)
This is the absorbing study of the rooting of the gospel in a culture, some of the by-products of that process. It is revealing of the background of the situation in Congo today. It is also revealing of how shallow is our talk of ?indigenous churches,? for few Christians can find it in their hearts to look tolerantly on a movement which is not made in their own image. This is not to say that everything in Kimbanguism is Christian. Neither is everything in Presbyterianism, Methodism, or Independent Missionism. But are there not signs that Christ has been, and remains, in some of the forms of prophetic Christianity in Congo?
Paid
Keywords: Christians – Africa; Congo (Democratic Republic) – Religion; Kimbangu; Simon; 1889?-1951